Ligustrazine Inhibits Lung Phosphodiesterase Activity in a Rat Model of Allergic Asthma. (10th January 2022) - Wang, Yajuan; Zhu, Huizhi; Tong, Jiabing; Li, Zegeng
Abstract : Objectives . This study sought to examine whether ligustrazine was capable of inhibiting phosphodiesterase (PDE) activity and improving lung function in a rat model of asthma. Methods . Rats were initially sensitized using ovalbumin (OVA) and then were challenged daily with aerosolized OVA beginning 14 days later (30 min/day) to generate a rat model of asthma. Changes in airway function following methacholine (MCh) injection were evaluated by monitoring lung resistance (R L ) and dynamic lung compliance (C dyn ) values using an AniRes2005 analytic system. In addition, serum IgE was measured via ELISA, while PDE expression was evaluated via qPCR and western blotting. Key Findings . Ligustrazine significantly impaired allergen-induced lung hyperresponsivity and inflammation in this asthma model system. Ligustrazine treatment was also associated with reduced expression of PDEs including PDE4 in the lungs of these rats. Conclusions . Ligustrazine suppresses airway inflammation and bronchial hyperresponsivity in this rat model system, and these changes are associated with decreased PDE expression at the protein and mRNA levels.